Calibration in Macroeconomics - Allan W. Gregory; Gregor W. Smith (Queen's University, Department of Economics, 1991)
This chapter reviews calibration techniques in macroeconomics. The discussion designs with an outline of the use of calibration in applied work. Next, a simple asset-pricing model is the setting for a demonstration of calibration and for comparison with conventional estimation and testing. Experiments with calibrated models may be formalized as Monte Carlo testing. With the asset-pricing model, we use simulation methods to calculate the exact size of the variance-bounds-type test proposed by Hansen and Jagannathan (1991). Finally, we suggest that calibration is best viewed as an informal guide to model reformulation
Keywords: 330